Assessment of bone marrow-derived Cellular Therapy in progressive Multiple Sclerosis (ACTiMuS): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Rice, Claire; Marks, David; Ben-Shlomo, Yoav; Evangelou, Nikos; Morgan, Paul; Metcalfe, Chris; Walsh, Peter; Kane, Nick; Guttridge, Martin; Miflin, Gail; Blackmore, Stuart; Sarkar, Pamela; et al.
Abstract Background We have recently completed an evaluation of the safety and feasibility of intravenous delivery of autologous bone marrow in patients with progressive multiple sclerosis (MS). The possibility of repair was suggested by improvement in the neurophysiological secondary outcome measure seen in all participants. The current study will examine the efficacy of intravenous delivery of autologous marrow in progressive MS. Laboratory studies performed in parallel with the clinical trial will further investigate the biology of bone marrow-derived stem cell infusion in MS, including mechanisms underlying repair. Methods/design A prospective, randomised, double-blind, placebo-controlled, stepped wedge design will be employed at a single centre (Bristol, UK). Eighty patients with progressive MS will be recruited; 60 will have secondary progressive disease (SPMS) but a subset (n  = 20) will have primary progressive disease (PPMS). Participants will be randomised to either early or late (1 year) intravenous infusion of autologous, unfractionated bone marrow. The placebo intervention is infusion of autologous blood. The primary outcome measure is global evoked potential derived from multimodal evoked potentials. Secondary outcome measures include adverse event reporting, clinical (EDSS and MSFC) and self-assessment (MSIS-29) rating scales, optical coherence tomography (OCT) as well as brain and spine MRI. Participants will be followed up for a further year following the final intervention. Outcomes will be analysed on an intention-to-treat basis. Discussion Assessment of bone marrow-derived Cellular Therapy in progressive Multiple Sclerosis (ACTiMuS) is the first randomised, placebo-controlled trial of non-myeloablative autologous bone marrow-derived stem cell therapy in MS. It will determine whether bone marrow cell therapy can, as was suggested by the phase I safety study, improve conduction in multiple central nervous system pathways affected in progressive MS. Furthermore, laboratory studies performed in parallel with the clinical trial will inform our understanding of the cellular pharmacodynamics of bone marrow infusion in MS patients and the mechanisms underlying cell therapy. Trial Registration ISRCTN27232902 Registration date 11/09/2012.NCT01815632 Registration date 19/03/2013